2019
DOI: 10.1111/jcmm.14744
|View full text |Cite
|
Sign up to set email alerts
|

miR‐148a suppresses inflammation in lipopolysaccharide‐induced endometritis

Abstract: Endometritis is a postnatal reproductive disorder disease, which leads to great economic losses for the modern dairy industry. Emerging evidence indicates that microRNAs (miRNAs) play a pivotal role in a variety of diseases and have been identified as critical regulators of the innate immune response. Recent miRNome profile analysis revealed an altered expression level of miR‐148a in cows with endometritis. Therefore, the present study aims to investigate the regulatory role of miR‐148a in the innate immune re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
30
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(32 citation statements)
references
References 54 publications
1
30
0
1
Order By: Relevance
“…MicroRNAs (miRNAs) are a type of single-stranded non-coding RNAs, which are typically about 22 nucleotides in length 6 , 7 . miRNAs can modulate gene expression through affecting the translation or stability of the target messenger RNAs (mRNAs) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…MicroRNAs (miRNAs) are a type of single-stranded non-coding RNAs, which are typically about 22 nucleotides in length 6 , 7 . miRNAs can modulate gene expression through affecting the translation or stability of the target messenger RNAs (mRNAs) 8 .…”
Section: Introductionmentioning
confidence: 99%
“…Bovine endometrial epithelial cells treated with LPS to induce an inflammatory response revealed a significant downregulation of both the miR-148a and the associated proinflammatory cytokines, IL-1ß and the TNF-α. Moreover, overexpression of miR-148a suppresses the activation of the NF-κBp56 pathway by targeted suppression of TLR-mediated pathway [ 83 ]. In the same study, it was shown that overexpression of miR-148a alleviated the uterine inflammation, making the miR-148a a potential therapeutic molecule for uterine inflammation and endometritis.…”
Section: Involvement Of Cellular and Extracellular Micrornas In Enmentioning
confidence: 99%
“…Considering the importance of innate immunity to the defense of the postpartum uterus, and the nature of most relevant uterine pathogens, the authors proposed that an adaptive immunity biased towards a Th17 response could enhance the ability of the innate immune system eliminate bacteria in the bovine endometrium after parturition (Machado and Silva, 2020). Another novel concept related to the development and progression of endometritis is differential expression of microRNAs (miR) (Jiang et al, 2020;Salilew-Wondim et al, 2016). MicroRNAs are a class of small non-coding single-stranded RNA molecules (usually 20-22 nucleotides in length) that bind to the 3′-untranslated regions or coding sequences of specific target mRNAs, thereby resulting in their translational repression or degradation.…”
Section: Advances On Understanding Of Uterine Diseases Pathogenesismentioning
confidence: 99%
“…A study characterized the profile of miR in dairy cows revealing that miR-148 had differential expression in cows with endometritis (Salilew-Wondim et al, 2016). A follow-up study reported that miR-148a expression in lipopolysaccharide-stimulated endometrial epithelial cells was reduced and overexpression of miR-148a using agomiR markedly lowered the proinflammatory cytokines, such as IL-1β and TNF-α (Jiang et al, 2020). Moreover, overexpression of miR-148a also suppressed NF-κB p65 activation by targeting the TLR4-mediated pathway.…”
Section: Advances On Understanding Of Uterine Diseases Pathogenesismentioning
confidence: 99%
See 1 more Smart Citation